Electron concentration effects on the Shastry-Sutherland phase stability in Ce 2 − x Pd 2 + y In 1 − z solid solutions - Sereni, Julian Gustavo Renzo (2011)
The stability of the Shastry-Sutherland (ShaSu) phase as a function of electron concentration is investigated through the field dependence of thermal and magnetic properties of the solid solution Ce2−xPd2+y In1−z on the antiferromagnetic (AF) branch. In these alloys, the electronic (holes) variation is realized by increasing Pd concentration. The AF transition TM decreases from 3.7 to 3.0 K as Pd concentration increases from y = 0.2 to 0.4. By applying magnetic field, the ShaSu phase is suppressed once the field-induced ferromagnetic polarization takes over at a critical field Bcr, which increases with Pd content. A detailed analysis around the critical point reveals a structure in the maximum of the ∂M/∂B derivative, which is related to an incipient step in the magnetization M(B) predicted by the theory for the ShaSu lattice. The crossing of M(B) isotherms, observed in ShaSu prototype compounds, is also analyzed. The effect of In substitution by Pd is interpreted as an increase in the number of “holes” of the conduction band and results in a unique parameter able to describe the variation of the magnetic properties along the studied range of concentration.